2021
DOI: 10.3390/jcm10051039
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Liver Function Test in Patients Infected with Coronavirus (SARS-CoV-2): A Retrospective Single-Center Study from Spain

Abstract: The outbreak of the novel coronavirus SARS-CoV-2 epidemic has rapidly spread and still poses a serious threat to healthcare systems worldwide. In the present study, electronic medical records containing clinical indicators related to liver injury in 799 COVID-19-confirmed patients admitted to a hospital in Madrid (Spain) were extracted and analyzed. Correlation between liver injury and disease outcome was also evaluated. Serum levels of Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Gamma-gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…According to our findings, the De Ritis ratio and age have a considerable positive association ( Supplement Table 1 ), which is in accordance with previous studies [ 14 , 20 ]. Surprisingly, the predictive function of the De Ritis ratio for mortality is more robust in patients younger than 60 years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to our findings, the De Ritis ratio and age have a considerable positive association ( Supplement Table 1 ), which is in accordance with previous studies [ 14 , 20 ]. Surprisingly, the predictive function of the De Ritis ratio for mortality is more robust in patients younger than 60 years.…”
Section: Discussionsupporting
confidence: 93%
“…A prior study from Turkey that investigated 554 patients with COVID-19 reported that the De Ritis ratio was a good predictor of hospitalization in the intensive care unit but did not predict mortality [ 13 ]. Another study from Spain found a higher De Ritis ratio in non-survivors of COVID-19 compared with that in the survivors [ 14 ]. In addition, Harsh et al found that De Ritis ratio at admission was a significant predictor of mortality [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact effect of COVID-19 on the liver is currently unclear, it can be noted that liver biochemistry abnormalities appear to be common in COVID-19 patients, affecting approximately 17-58% of individuals with COVID-19 [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] (Table 1). Liver biochemistry abnormalities manifest primarily as mild and moderate elevations of alanine aminotransferase (ALT) and/or aspartate aminotransferase (AST) in the early stages of the disease [25,[48][49][50].…”
Section: Covid-19 and Liver Dysfunctionmentioning
confidence: 99%
“…Earlier studies showed that elevated AST than ALT is more common in patients with COVID-19, which correlates with our findings. 4 , 7 , 14 , 21 , 22 We also found that patients with elevated AST had poorer prognoses than those with elevated ALT. In a retrospective study of 2073 hospitalized COVID-19 patients from China, among all liver parameters, only elevated AST and direct bilirubin levels were associated with in-hospital mortality with adjusted hazard ratio = 1.61 (95% CI: 1.20–2.15; p = 0.001) and adjusted hazard ratio = 1.57 (95% CI: 1.14–2.16; p = 0.006), respectively.…”
Section: Discussionmentioning
confidence: 51%